THE EFFECTS OF XYLANASE SUPPLEMENTATION ON MEAT QUALITY, CARCASS RECOVERY AND BLOOD CHOLESTEROL IN BROILERS FED ON WHEAT-BASED DIETS - Hanim, Chusnul (2013)
This study was conducted to investigate the effects of xylanase supplementation on meat quality, carcass recovery and blood cholesterol in broilers fed on wheat-based diets. The experimental diets consisted of a wheat-based diet. Four isoenergetic and isonitrogenous diets consisting of control diet without enzyme and three test diets supplemented with xylanase at 0, 0.75, 1.5 or 2.25 g/kg enzyme preparation (xylanase activity was 60.30 U/g). The diets were fed between 14 and 42 days of age. Each diet was offered to 3 replicates of 5 Lohmann broiler chicks in a randomized one way design. Data was analyzed using SPSS for one-way design. Enzyme used in the study was semi-purified having xylanase activity 62.03 U/g. Xylanase supplementation had no significant effect (p>0.05) on carcass recovery and meat quality in bloilers fed on wheat-based diets. The treatment increased (P<0.01) concentration of blood cholesterol contrast to control, and tended to increase (P<0.1) meat protein content and abdominal fat pad. In conclusion, enzyme supplementation contributed few responses in birds when supplemented at three levels. Keywords:Xylanase, Broilers, carcass recovery,